Differential gene regulation in the anterior cingulate cortex and superior temporal cortex in schizophrenia: A molecular network approach - Gebicke-Härter, Peter J.; Leonardi-Essmann, Fernando; Haerter, Jan O.; Rossner, Moritz J.; Falkai, Peter; Schmitt, Andrea; Raabe, Florian J. (Schizophrenia research, 2021)
The closely connected anterior cingulate cortex (ACC) and superior temporal cortex (STC) are important for higher cognitive functions. Both brain regions are disturbed in schizophrenia, i.e., functional and structural alterations have been reported. This postmortem investigation in brains from patients with schizophrenia and controls compared gene expression in the left ACC and left STC. Most differentially expressed genes were unique to each brain region, but some clusters of genes were equally dysregulated in both, giving rise to a more general disease-specific pattern of gene regulation. The data was used to construct a molecular network of the genes identically expressed in both regions as primary nodes and the metabolically connected genes as secondary nodes. The network analysis identified downregulated clusters of immune-associated gene products and upregulated clusters belonging to the ubiquitin-proteasome system. These findings could help to identify new potential therapeutic targets for future approaches.